Arbuscular mycorrhizal fungi inoculation exerts weak effects on species- and community-level growth traits for invading or native plants under nitrogen deposition - Guo, Xiao; Li, Mingyan; Jiang, Siyu; Yang, Liyu; Guo, Shaoxia; Xing, Lijun; Wang, Tong (Frontiers in Ecology and Evolution, 2023)
Nitrogen deposition and biological invasion are two major components of global environmental change. Nitrogen deposition has been considered to enhance the resource availability of recipient habitats, which influences the invasiveness of plant invader and the invasibility of recipient native communities. Nitrogen deposition has been shown to reduce the relative abundances of arbuscular mycorrhizal fungi (AMF) globally. AMF have been found to mutualistically symbiose with approximately 75% of plant species and act as a nutrient supplier. AMF may modify the structure of native plant communities, collaborate with alien plant invaders and thus promote their invasion. The alien woody invader, Rhus typhina L. has been introduced into North China as a horticultural species, invaded the native plant community and outperformed the native competitors in growth and in photosynthetic efficiency. Nevertheless, little is known about if nitrogen deposition and AMF inoculation synergistically alter the invasibility of native plant community. In this study, R. typhina was subjected to the artificial plant community assembled by four co-existing native species -Chenopodium album L., Vitex negundo var. heterophylla (Franch.) Rehd., Rhus chinensis Mill. and Acer truncatum Bunge in a mesocosm experiment.Nitrogen deposition and AMF inoculation were simulated as environmental and biotic filters respectively. Aboveground biomass and biomass proportion, reflecting plant growth and performance, and specific leaf area and chlorophyll concentration correlated with carbon use and photosynthetic capacity of both the alien invader and the native plants were measured and calculated after harvest. We found that AMF inoculation did not alter the trait variation of alien and native species to increasing nitrogen deposition level in general, although AMF inoculation impeded the increase of aboveground biomass for C. album, V. negundo and native community with increasing nitrogen deposition level. In the scenario of nitrogen deposition and AMF inoculation, a stable status of invasion dynamic may be maintained and needs to be checked with integration of traits at extended temporal scale.